Falciparum malaria mortality in sub-Saharan Africa in the pretreatment era - Watson J.A. (2023)
Driven by the malaria-protective effect of sickle-cell trait, balancing selection results in hemoglobin S equilibrium allele frequencies of between 15% and 20% in areas of high Plasmodium falciparum transmission in sub-Saharan Africa. From this we estimate that the malaria-attributable childhood mortality in the pretreatment era was between 15% and 24%.